Caught on the Hop: Politico-philosophical Writing of the 'Leap'. Issue 3 (September 2022) - Wortham, Simon
Abstract : This essay reads Derrida's Geschlecht III: Sex, Race, Nation, Humanity in the context of the philosophical and political legacies associated with the motif of leaping. Surveying the philosophical and textual 'politics' of this figure of the leap in the work of Kierkegaard, Hegel, Marx, Freud, Heidegger and others, the essay tracks its connection to the question of philosophical nationalism (and associated images of place, ground and gathering) explored by Derrida in Geschlecht III, speculating on the ambivalent resonances that 'leap' across the political spectrum.